Types of Slips of the Ear in The Hardware Shop Episode of The Two Ronnies British Sketch Comedy (Jurnal Pustaka, 2026)
This study investigated the phenomenon of slips of the ear within The Hardware Shop episode of The Two Ronnies British sketch comedy, aiming to identify the types of slips present in the sketch. A qualitative research method was employed, utilizing observation, documentation, and transcription techniques to collect data from the spoken utterances in the chosen comedy sketch. The data analysis applied a descriptive qualitative approach, classifying slips of the ear based on Bond's (2005) speech perception error theory. The analysis revealed that humor rooted in slips of the ear was a significant comedic element in the sketch. Specifically, three types of speech perception errors were identified from Bond's (2005) classification: word boundary misperception, consonant misperception, and content and function word misperception. Consonant misperception and content word misperception emerged as the most prominent types, largely due to their role in creating verbal and phonological ambiguity. These errors were intentionally scripted, effectively generating comedic misunderstandings. This research demonstrated how psycholinguistic phenomenon, when deliberately integrated into scripted comedy, served as a powerful tool for humor creation.